Sharia Compliance in Eco-Marketing: A Fiqh Analysis of Sustainable Eco-Business Practices - Musta’an Al Faruqi; May Shinta Retnowati (Indonesian Journal of Law and Islamic Law (IJLIL), 2026)
Fiqh is used as a reference for Muslims in living their lives in accordance with the rules set by Allah SWT, including consumption activities. Meeting consumption needs is fair if it is in accordance with needs and not excessive. Aggressive marketing strategies often trigger consumerist behavior in consumers to buy 'environmentally friendly' products excessively, which actually contradicts the principles of tabzir and israf.  The purpose of this study is to analyze the Sharia compliance of marketing that highlights 'eco-friendly' labels to increase sales, which can trap consumers into 'green hedonism' (buying environmentally friendly products beyond their needs), reviewed from the perspective of Fiqh concepts. This research uses a normative legal method with an empirical approach, often referred to as socio-legal research. Data was obtained through in-depth interviews, observations of their promotional activities, and documentation on advertisements, analyzed in a descriptive-analytical. This finding addresses doubts about the concept of 'green hedonism' through fiqh compliance in marketing transactions, indicating that during the implementation of eco-marketing strategies, this study found that Jari Hitam Ecoprint mitigates these risks not only by highlighting labels but also by educating consumers about the utility value and sustainability of the products. The eco-label changes function, not merely as an aggressive promotional tool but also as an educational medium. It ensures that consumers' intention to buy environmentally friendly products is based on the principle of fiqh, not merely on lifestyle labeling.